(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Siddha system of medicine is a traditional medicinal system followed in South India. In a human body imbalance of humours causes various diseases with major symptoms. We found out the disease by the signs of symptoms and curable by Siddha medicines. Purgation is one of the major treatments of Siddha system. Purgation medically induced elimination of stools to calm down excessive vitiated Dosha. Though purgation is used in modern system it is mainly confined to gastro intestinal diseases. But in Siddha system purgation is used in first line of treatment for many diseases. In this article, purgation based on medicines, various methods of purgation, procedures of purgation, different diseases, contra indications, signs and symptoms of inadequate purgation, excessive purgation and complication and dietary regimens is explained in a holistic manner. Siddha literature and published papers were explored to found the rationale of purgation treatment. Purgation is one of the advisable therapies for chronic diseases. Purgative medicines making in the form of Kudineer, Kuzhambu and oil. Agasthiyar Kuzhambu is essentially for purgation treatment. This medicine helps to cure fifty four various diseases like fever, cough, bleeding piles etc.